Functional imaging with 11C-metomidate PET for subtype diagnosis in primary aldosteronism. Issue 6 (December 2020) - Soinio, Minna; Luukkonen, Anna-Kaarina; Seppänen, Marko; Kemppainen, Jukka; Seppänen, Janne; Pienimäki, Juha-Pekka; Leijon, Helena; Vesterinen, Tiina; Arola, Johanna; Lantto, Eila; Helin, Semi; Tikkanen, Ilkka; et al.
Abstract : Objective: Endocrine Society guidelines recommend adrenal venous sampling (AVS) in primary aldosteronism (PA) if adrenalectomy is considered. We tested whether functional imaging of adrenal cortex with 11 C-metomidate ( 11 C-MTO) could offer a noninvasive alternative to AVS in the subtype classification of PA. Design: We prospectively recruited 58 patients with confirmed PA who were eligible for adrenal surgery. Methods: Subjects underwent AVS and 11 C-MTO-PET without dexamethasone pretreatment in random order. The lateralization of 11 C-MTO-PET and adrenal CT were compared with AVS in all subjects and in a prespecified adrenalectomy subgroup in which the diagnosis was confirmed with immunohistochemical staining for CYP11B2. Results: In the whole study population, the concordance of AVS and 11 C-MTO-PET was 51% and did not differ from that of AVS and adrenal CT (53%). The concordance of AVS and 11 C-MTO-PET was 55% in unilateral and 44% in bilateral PA. In receiver operating characteristics analysis, the maximum standardized uptake value ratio of 1.16 in 11 C-MTO-PET had an AUC of 0.507 ( P =  n.s.) to predict allocation to adrenalectomy or medical therapy with sensitivity of 55% and specificity of 44%. In the prespecified adrenalectomy subgroup, AVS and 11 C-MTO-PET were concordant in 10 of 19 subjects with CYP11B2-positive adenoma and in 6 of 10 with CYP11B2-positivity without an adenoma. Conclusions: The concordance of 11 C-MTO-PET with AVS was clinically suboptimal, and did not outperform adrenal CT. In a subgroup with CYP11B2-positive adenoma, 11 C-MTO-PET identified 53% of cases. 11 C-MTO-PET appeared to be inferior to AVS for subtype classification of PA.